ANALYSIS ON DIFFERENT TYPES OF VISCOMETERS, DESIGN, MATERIALS AND TECHNOLOGY - S. Aruna, G. Shantha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A possible quality control parameter for a simple and quick fluid evaluation is a viscosity as a sensitive measurement of fluid changes. Viscosity measurement is important both as a potential hemodynamic biomarker for quality assurance for liquid products and for the monitoring of viscosity of clinical fluids. In order to test kerosene, ethanol and plasma, the fabricated viscometer yielded the following findings; respectively 0.00134, 0.0011 and 0.0034. These values are closely related to various literature and a significant average 5.9% error.This demonstrates that the produced viscometer is reliable and compliant and can be used for laboratory, building, food processing, and education purposes. Even after so much development, the choice of best production systems in terms especially of simplifying the process, cost and time is also one of the constant challenges facing the development of micro-fluidic devices. Here is a 3-D electrofluidic viscometer printed (EMV).By automatically evaluating the transit time of the sample fluid versus the reference fluid viscosity under laminar flow, the EMV measures it. We disregard the various types of viscometers, design, materials and technology in this paper.